2018
DOI: 10.3389/fgene.2018.00531
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Neurological and White Matter Changes and Premutation Status Categories of Older Male Carriers of the FMR1 Alleles Are Linked to Genetic (CGG and FMR1 mRNA) and Cellular Stress (AMPK) Markers

Abstract: The fragile X premutation (PM) allele contains a CGG expansion of 55–200 repeats in the FMR1 gene’s promoter. Male PM carriers have an elevated risk of developing neurological and psychiatric changes, including an approximately 50% risk of the fragile X-associated tremor/ataxia syndrome (FXTAS). The aim of this study was to assess the relationships of regional white matter hyperintensities (wmhs) semi-quantitative scores, clinical status, motor (UPDRS, ICARS, Tremor) scales, and cognitive impairments, with FMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(46 citation statements)
references
References 64 publications
13
33
0
Order By: Relevance
“…Notably, when taken together with our previous study (19), the current findings imply a continuity in the clinical and white matter changes extending from non-affected older male carriers, to non-syndromic forms separate from FXTAS, and eventually to the full manifestation of FXTAS. Moreover, the finding of significant correlations between the wmhs in infratentorial regions and the motor and cognitive scores in the total sample of PM carriers suggests that the underlying primary pathology might be initially confined to this region.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Notably, when taken together with our previous study (19), the current findings imply a continuity in the clinical and white matter changes extending from non-affected older male carriers, to non-syndromic forms separate from FXTAS, and eventually to the full manifestation of FXTAS. Moreover, the finding of significant correlations between the wmhs in infratentorial regions and the motor and cognitive scores in the total sample of PM carriers suggests that the underlying primary pathology might be initially confined to this region.…”
Section: Discussionsupporting
confidence: 83%
“…This suggests that white matter alterations may serve as sensitive markers of incipient decline to FXTAS, or to asyndromic neurological manifestations not meeting the diagnostic criteria for FXTAS. This aspect was discussed in our earlier publication (19), where we reported an example of the presence of the MCP sign in some non-FXTAS PM carriers, consistent with similar observations in five such individuals most recently reported by Famula et al (20).…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data on progression of the premutation-associated changes from sub-symptomatic to clinical forms, especially in females, may have an important impact on future research, as well as on clinical approaches, because it introduces the concept of continuity. Combined with earlier evidence for the existence of subclinical neural or metabolic changes in both male and female carriers over a broad age range (Tassone et al, 2012 ; Wang et al, 2012 , 2013 , 2017 ; Battistella et al, 2013 ; Shelton et al, 2016 ; Loesch et al, 2017 , 2018 ; Hocking et al, 2019 ; O'Keeffe et al, 2019 ), these data have shown that the focus of such research should be on trajectories rather than on the final outcome of the premutation-associated process. The most recent study, based on a wide range of metabolic and proteomic biomarkers, showed a decline of mitochondrial activities in pre-symptomatic female PM carriers, leading the authors to the conclusion that the development of neurodegeneration or other clinical symptoms in older carriers could be linked to a lifetime accumulation of cellular damage, aggravated by the aging process (Napoli et al, 2020 ).…”
Section: Discussionmentioning
confidence: 62%